A survey of the Public Administration Library collection of eleven ASAP member schools in Metro Manila - Pantola, Alicia T. 1945- (1996)
Based on these findings, some conclusions were drawn: 1) the amount of library fees, source of library funds and percentage of the total book fund alloted for the acquisition of public administration materials influence the growth of the collection; 2) some library heads have no professional qualification in the field of library science; 3) awareness of the field of public administration affects the extent of public adminstration collection by subject-area as familiarity with the public administration sub-fields provides the librarian a basis for acquisition; 4) the number of years of the school establishment somehow indicate the extent of the collection in terms of volume as illustrated in the case of UP CPA and Greenville College which are the oldest and the youngest public administration schools in the country, respectively; 5) the number of modes applied in acquiring and manner of ordering affect the volume generated by the library.
Findings and recommendations provided in this study will serve as basis for program development in order to improve the collection of the libraries concerned.
The data reveal the strengths and weaknesses of the eleven libraries surveyed. The University of the Philippines is the only educational institution which has an independent college and library for public administration. Majority of the head librarians have master's degree in library science. Majority of the eleven libraries surveyed have a professional librarian specifically assigned to manage public administration collection. The most commonly used cataloging rule is AACR 2.5. Only three libraries have a written collection management policy statement for public administration. On the average, the eleven libraries being surveyed serve 10.18 hours per day and 6.09 days per week. Only four have special collections while the remaining seven do not have any. Majority of the libraries surveyed rely on gifts/donations and purchase in acquiring library materials on public administration while only a few acquire library materials through exchange and interlibrary loans. Likewise, the majority order books through jobbers and directly to the publisher while a few likewise order books through exhange and interlibrary loan. The source of funds of the majority of the libraries being surveyed is library fees while some source from fines, budgetary appropriation, donations and benefits from a foundation. On the average, the eleven libraries collect P214.50 per semester. UP CPA ranks the highest, setting aside 80 percent of its library funds for public administration materials and the remaining 20 percent for related fields, references and Filipiniana. UP CPA library maintains the biggest collection at 44,942 while Greenville College library has the smallest collection at 560. The three subject-areas in public administration which constitute the largest number of collection are international relations, organization and management and sociology and social development. Public administration in general only ranks sixth in terms of volume which is recorded at 1,903. Only five participated in interlibrary cooperative collection development with other libraries. Majority of the library users-respondents believe that their respective libraries are accessible and that the size of their respective libraries is enough in relation to the number of library users.
The researcher recommends the following: 1) the eleven libraries surveyed should have an interlibrary cooperative collection development which may be initiated by the Association of Public Administration Schools in the Philippines; 2) the library personnel must be given continuing training/seminars on librarianship and development of public administration as a field of study; 3) the library collection in general public administration should be given paramount attention; 4) the eleven libraries surveyed should employ optimum modes of acquiring and ordering books to assure getting maximum results in terms of increasing public administration collection; and 5) increasing the library fund, library fee and other sources of support should be considered in order to increase the allotment for acquisition of library materials for public administration.
This study provides a brief historical background of the eleven ASPAP (Association of Schools of Public Administration in the Philippines) member schools in Metro Manila and the library which serves as a support institution providing reference materials for sound education and research needs. Focus is given to administration and organization, library personnel (qualification of chief/head librarians and the number of staff), library services, technical services, manner of acquisition and mode of ordering library materials, library funds/fees, source of funds, percentage of the total book fund alloted for acquisition of public administration collection, extent of the library collection (by type of materials and by subject-areas) and interlibrary cooperative collection development. Library users evaluation of the accessibility and size of the library with respect to the library users was also gathered. The questionnaire was used to gather data on the above-mentioned concerns.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Association of Schools of Public Administration in the Philippines (ASPAP); Libraries -- Evaluation. -- Philippines -- Manila Metropolitan Area